Access to Plant Genetic Resources and Maintaining International Food Security - M. N. Kopylov; N. N. Emelyanova (Московский журнал международного права, 2012)
Today, breeders and patent owners through the mechanisms of intellectual property rights receive monopoly privileges which encourage the implementation of innovation in plant breeding. During this process, the least well-off farmers can become even more dependent on means of production. In this article the question how seeds policy of states can contribute to realization of human right to food is considered, it is indicated how to make most effective use of researches in developing countries for the least wealthy farmers, and how to regulate commercial seed farms in the interests of the right to food and food security.